Management of Patients Hospitalized for Diabetic Foot Infection: A Local Evaluation - AmirHooshang Zargarzadeh; Sina Sabzevari; Farzin Khorvash; Azadeh Moghaddas (Research Center for Rational Use of Drugs (RCRUD), 2018)
Background: Diabetic foot ulcer (DFU) is the most frequent complication of DM with an upward trend over the last two decades.The present study was implemented to determine how DFU was managed in a major referral hospital in Isfahan. Methods: This prospective cross-sectional study was conducted from the 1st July 2016 to 15th December 2017 in Al-Zahra Hospital, in Isfahan, Iran. The information was collected by atrained pharmacy student by recordingbaseline characteristics of patients, current approach to investigate the DFU, management of the infected wound, and assessment of risk factors related to patients' outcomes. Results: The mean (±S.D) age of patients was 59.13±10.80 years. The majority of our patients had affected with Type 2 DM (96.3 %). Most of the patient (61%) had wound with grade 3 in the Wagner classification. Lesions mainly involved toes (46.3%). The most lesions (42%) had a mean size of the 5-10 cm2.The most frequently prescribed combination antibiotics were meropenem and Targocid® (teicoplanin) (34.1%), Tazocin® (piperacillin + tazobactam) and Targocid® (24.3%). Mean (±SD) duration of parenteral therapy (alone or in associated with oral treatment) was 14.95±7.62 days. Ulcer size (cm2) (P=0.04), and Wagner classification (P=0.012) had significant association with unhealed ulcer.  Conclusion: Although, our diabetic center is university-affiliated, there are still several points, and pitfalls must be considered and revised in DFU patients. Obtaining microbiological sampling, antibiotic management and baseline assessment of wound in patients are the most troublesome complications discovered by our investigation.